Effects of Grazing Enclosures on Species Diversity, Phenology, Biomass, and Carrying Capacity in Borana Rangeland, Southern Ethiopia - Fenetahun, Yeneayehu; Yuan, You; Xinwen, Xu; Yongdong, Wang (Frontiers in Ecology and Evolution, 2021)
A grazing enclosure (GE) is one of the most effective techniques for restoring degraded rangelands by modifying the composition, abundance, and diversity of species. However, the effect of GEs on different grazing intensities and durations compared to open-grazing (OG) rangelands is not well known. We aimed to assess the effect of GE on the characteristics of plant species. We established five plots in a short-term enclosure, a long-term enclosure, and an OG treatment to examine the effect of GE on vegetation species’ height, abundance, diversity, phenology, biomass, heterogeneity, and the carrying capacity (CC) of rangeland under grazed and enclosed conditions. We found that GE significantly (P < 0.05) increased vegetation height, abundance, biomass, CC, phenological period, and species diversity. However, the increase in height, diversity, and phenological periods were not consistent with enclosure duration, and higher increments were recorded at the short-term enclosure site. The highest Shannon index value recorded at StGE (2.45) was 28.6 and 12.2% greater than the LtGE (1.75) and OG (2.15) sites, respectively. The advanced phenological periods were higher at the StGE site and showed 22.6 and 60.3% higher values than the LtGE and OG sites, respectively. The highest carrying capacities of 23.4 and 114.3% for livestock were observed at the LtGE compared to the StGE and OG grazing sites. In addition, the heterogeneity of the plants’ community was significantly higher in the long-term GE, due to the decrease in species’ diversity. In conclusion, this paper further contributes to the development of the theoretical basis on the effects of GEs and recommends strategies like rotational grazing and reseeding to be used in tandem with a GE for sustainable management of rangelands.